Quality - Information Technologies - Consumer - Vasile Dinu (Amfiteatru Economic)
Companies and consumers live in a world where the Internet is one of its defining elements, information technologies increasingly marking all the activities undertaken by them. With increased access to information, with a strong desire for knowledge, and with increased standards, both companies and consumers pay an important attention to quality and information technologies, which are, on the one hand, a sure path to success for an entrepreneur and, on the other hand, the confirmation of a correct choice for a consumer. Therefore, in a society increasingly characterized by words and phrases such as “information”, “internet”, “social media”, “standards”, the orientation of the academic environment towards research in the fields of quality, information technologies, and consumer is inevitable. This special number of the journal highlights the concern of a series of researchers in the economics area on specific issues, respectively regarding aspects associated with quality, information technologies, and consumer